2021
DOI: 10.3389/fphar.2021.736986
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Economic Evaluations of Active Tuberculosis Treatments

Abstract: Background: The disease burden of active tuberculosis (TB) is considerable, but systematic reviews of economic evaluations of active TB treatments are scarce.Methods: PubMed, EMBASE, and the Cochrane Library databases were used to search for articles on cost-effectiveness analysis or cost-utility analysis that economically evaluated active TB treatments, which were then systematically reviewed by two independent reviewers. We extracted vital components of the included studies, such as country, population, inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 61 publications
(264 reference statements)
0
7
0
Order By: Relevance
“…Moreover, TB has been one of the top 10 causes of death and the leading cause of death from a single infectious agent worldwide (WHO, 2020). Drug-resistant-TB (DR-TB), a resistance of M.tb to one or more anti-tuberculosis drugs, is reported as the main challenge in TB treatment that significantly impacts the clinical and economic aspects of the patients (Pradipta et al, 2019a(Pradipta et al, , 2019bWHO, 2020;Byun et al, 2021). A global meta-analytical study from our group verified that TB patients previously treated for TB have a higher risk of developing multi-drug-resistant TB (MDR-TB) (Pradipta et al, 2018).…”
Section: Introductionmentioning
confidence: 67%
“…Moreover, TB has been one of the top 10 causes of death and the leading cause of death from a single infectious agent worldwide (WHO, 2020). Drug-resistant-TB (DR-TB), a resistance of M.tb to one or more anti-tuberculosis drugs, is reported as the main challenge in TB treatment that significantly impacts the clinical and economic aspects of the patients (Pradipta et al, 2019a(Pradipta et al, , 2019bWHO, 2020;Byun et al, 2021). A global meta-analytical study from our group verified that TB patients previously treated for TB have a higher risk of developing multi-drug-resistant TB (MDR-TB) (Pradipta et al, 2018).…”
Section: Introductionmentioning
confidence: 67%
“…Thus, we started by conducting a rapid review to identify the most relevant and recent systematic review that aligns with our review protocol to update it. Through this initial stage, we identified that the most recent systematic review of interventions for active TB was the one performed by Byun et al, which identified relevant economic evaluations published until January 1st, 2020 ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
“…As the scope of Byun et al review covered both pharmacological and non-pharmacological treatment strategies and interventions for active TB, we only focused on its included studies involving pharmacological interventions ( 15 ). We then conducted a systematic search to identify all relevant economic evaluations published after its search cut-off date until June 2022.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycobacterium tuberculosis ( Mtb ) is one of the lethal infectious pathogens accountable for the leading cause of mortality in developing countries (Behr et al, 2021; Byun et al, 2021; Jaganath et al, 2022; Kaufmann, 2021; Li et al, 2020; Pai et al, 2016). As per the World Health Organization (WHO) global tuberculosis report, in 2022, tuberculosis is accountable for 1.4 million deaths among human immunodeficiency virus (HIV)‐negative people and 0.18 million deaths among HIV‐positive people (World Health Organization, 2022).…”
Section: Introductionmentioning
confidence: 99%